The correlation of crude corrosivity in different field service environments with hydrogen flux measurements - Serate, Duane Go
This study provides the theoretical analysis and field results of a prototype real-time portable hydrogen collector method, called Hydrosteel. This instrument detects and measures the hydrogen diffusion through steel, as a result of napthenic acid corrosion (NAC) from high Total Acid Number (TAN) crudes